Analisis Buckling pada Rangka Mesin Pemberi Pakan Ikan otomatis - Yahdil; Fadhli Dzil Ikram; Wirya Sarwana (Program Studi Teknik Mesin Fakultas Rekayasa Sistem Universitas Teknologi Sumbawa, 2024)
Food security is a problem that the world will face in the future. One solution to address the issue of food security globally is in the fisheries sector. Indonesia is considered a solution as it is the second largest fish producer in the world, as stated by the FAO in The State of World Fisheries and Aquaculture 2022 report. However, in order to increase fish production, aquaculture needs to be conducted to maintain the stability of fisheries in Indonesia. To facilitate this process, an automatic fish feeder device is required. This device needs to undergo research, specifically in the field of buckling analysis. Buckling is a failure phenomenon that occurs due to compressive pressure on a structure, causing a change in its shape in the form of lateral deflection to another equilibrium form. In this analysis, calculations are performed for critical loads, deformation, and equivalent stress. The applied load on the frame is 100 kg or 981 N. The obtained critical load for frame type 1 with a cross-sectional area of 40 mm x 40 mm x 0.5 mm is 13.879,923 N, while for frame type 2 with a cross-sectional area of 40 mm x 25 mm x 0.5 mm, the critical load is 12.621,791 N. The maximum deformation for frame 1 is 0.25013 mm, and the minimum deformation is 0 mm. For frame 2, the maximum deformation is 0.53323 mm, and the minimum deformation is 0 mm. The maximum equivalent stress for frame 1 is 180.38 MPa, and the minimum equivalent stress is 0.0046383 MPa. The maximum equivalent stress for frame 2 is 99,735 MPa, and the minimum equivalent stress is 0.0016464 MPa.